Panel data model comparison for empirical saving-investment relations - Helmut Herwartz; Fang Xu (Kiel University, Department of Economics, 2006)
The low capital mobility among OECD countries, signalled by a high saving-investment (SI) relation and known as the Feldstein-Horioka puzzle, has triggered a lively discussion in the empirical literature. In this paper, we compare between, pooled, time and country dependent specifications of the SI relation via cross-validation criteria. It is found that the country dependent model is best performing among the four. Secondly, error correction models are uniformly outperformed by static panel models. Thirdly, via scatter diagrams of cross section specific estimates we observe a different time evolution of SI relations for developed and developing economies.
Keywords: C33; E22; E21; 330; Saving-investment relation; Feldstein-Horioka puzzle; model comparison; Panel; Ökonometrisches Modell; Vergleich; Sparen; Investition; Internationale Kapitalmobilität; Schätzung; OECD-Staaten; Feldstein-Horioka Puzzle